Feminism in the discourse of Asma Barlas : an analysis from an Islamic perspective - Rashad, Aisha Mohamed (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
The discourse on feminism among Muslims is gaining momentum around the world. While there are Muslims who identify themselves and their work within the feminist paradigm, there are others who resist such labels. Nonetheless, the works of these Muslims reflect feminist ideas. These Muslim feminists offer a feminist hermeneutical method to interpret the Qur'an. This hermeneutical method is claimed and portrayed to be under an Islamic paradigm. Asma Barlas is among those who champion this recourse to the classical exegeses that have been accepted by Muslims for generations. She argues that classical exegetes read the Qur'an in a way that gives men privilege over women and oppresses them. Accordingly, she offers her hermeneutics which she believes would liberate women and provide gender equality. This study assesses her hermeneutical method in light of Islamic perspective using classical texts as well as contemporary texts. Similarly, it examines the effect of Western feminism on Barlas ideas and her views. More specifically, it examines how the principles and concepts of Western feminism have influenced Barlas rereading of the Qur'an. The study also examines Barlas' reinterpretation of verses related to the veil, husband's authority, and polygyny. The method utilized in this study is textual/content analysis. The research has obtained several findings. Firstly, Barlas arguments against classical exegeses are weak as she relies on secondary sources, most of which are from orientalists, to substantiate her claims rather than delving into the original sources to verify them. Secondly, Barlas' own hermeneutics is faulty as she disregards authentic sources such as the alhadith in her reading. Moreover, in her attempt to read gender equality into the Qur'an, Barlas deviates from the established principles of Qur'anic exegesis. Finally, the study has found that Barlas has been largely influenced by Western feminism. More specifically, Judeo-Christian feminist theologies have been crucial in her reading of the Qur'an.